Thermal Modernization of the Panel Buildings External Walls - Filonenko, Olena; Yurin, Oleg; Kodak, Olga (International Journal of Engineering and Technology, 2018)
The thermal protection level of the first mass series panel buildings (series 111-94) is the lowest among residential buildings in Poltava. The problems of these buildings’ thermal modernization, is consideration of heat-conducting inclusions effect on the reduced resistance to heat transfer. In the studies such heat-conducting inclusions as the panel joints’ design, the window slope and the external wall geometry (the external corner) were taken into account. Studies were performed for the four pattern sections of the outer wall. Panels of two thickness variants with two joint designs were under consideration.To analyze the thermal protection level, the results of the two-dimensional temperature fields’ calculations were used. The analysis of the wall panels’ thermal protection level before the thermal modernization was performed. The magnitude of the heat conducting inclusions effect on reduced resistance of the walling to the heat transfer before and after the thermal modernization is determined. Possible ways of improving the wall panels’ heat-protective properties to the level of the standards in Ukraine are considered. The optimal variant of insulation for each pattern was chosen.